Comparison of Novel and Established Nitrification Inhibitors Relevant to Agriculture on Soil Ammonia- and Nitrite-Oxidizing Isolates - Papadopoulou, Evangelia S.; Bachtsevani, Eleftheria; Lampronikou, Eleni; Adamou, Eleni; Katsaouni, Afroditi; Vasileiadis, Sotirios; Thion, Cécile; Menkissoglu-Spiroudi, Urania; Nicol, Graeme W.; Karpouzas, Dimitrios G. (Frontiers in Microbiology, 2020)
Nitrification inhibitors (NIs) applied to soil reduce nitrogen fertilizer losses from agrο-ecosystems. NIs that are currently registered for use in agriculture appear to selectively inhibit ammonia-oxidizing bacteria (ΑΟΒ), while their impact on other nitrifiers is limited or unknown. Ethoxyquin (EQ), a fruit preservative shown to inhibit ammonia-oxidizers (AO) in soil, is rapidly transformed to 2,6-dihydro-2,2,4-trimethyl-6-quinone imine (QI) and 2,4-dimethyl-6-ethoxy-quinoline (EQNL). We compared the inhibitory potential of EQ and its derivatives with that of dicyandiamide (DCD), nitrapyrin (NP), and 3,4-dimethylpyrazole-phosphate (DMPP), NIs that have been used in agricultural settings. The effect of each compound on the growth of AOB (Nitrosomonas europaea, Nitrosospira multiformis), ammonia-oxidizing archaea (AOA) (“Candidatus Nitrosocosmicus franklandus”, “Candidatus Nitrosotalea sinensis”), and a nitrite-oxidizing bacterium (NOB) (Nitrobacter sp. NHB1), all being soil isolates, were determined in liquid culture over a range of concentrations by measuring nitrite production or consumption and qPCR of amoA and nxrB genes, respectively. The degradation of NIs in the liquid cultures was also determined. In all cultures, EQ was transformed to the short-lived QI (major derivative) and the persistent EQNL (minor derivative). They all showed significantly higher inhibition activity of AOA compared to AOB and NOB isolates. QI was the most potent AOA inhibitor (EC50=0.3-0.7 μM) compared to EQ (EC50=1-1.4 μM) and EQNL (EC50=26.6-129.5 μM). The formation and concentration of QI in EQ-amended cultures correlated with the inhibition patterns for all isolates suggesting that it was primarily responsible for inhibition after application of EQ. DCD and DMPP showed greater inhibition of AOB compared to AOA or NOB, with DMPP being more potent (EC50=221.9-248.7 μΜ vs EC50=0.6-2.1 μΜ). NP was the only NI to which both AOA and AOB were equally sensitive with EC50s of 0.8-2.1 and 1.0-6.7 μM, respectively. Overall, EQ, QI and NP were the most potent NIs against AOA, NP and DMPP were the most effective against AOB, while NP, EQ and its derivatives showed the highest activity against the NOB isolate. Our findings benchmark the activity range of known and novel NIs with practical implications for their use in agriculture and the development of NIs with broad or complementary activity against all AO.